Evaluation of CarbonTracker's Inverse Estimates of North American Net Ecosystem Exchange of CO2 From Different Observing Systems Using ACT‐America Airborne Observations. Issue 12 (16th June 2021) - Cui, Yu Yan; Jacobson, Andrew R.; Feng, Sha; Wesloh, Daniel; Barkley, Zachary R.; Zhang, Li; Gerken, Tobias; Keller, Klaus; Baker, David; Davis, Kenneth J
Abstract: Quantification of regional terrestrial carbon dioxide (CO2 ) fluxes is critical to our understanding of the carbon cycle. We evaluate inverse estimates of net ecosystem exchange (NEE) of CO2 fluxes in temperate North America, and their sensitivity to the observational data used to drive the inversions. Specifically, we consider the state‐of‐the‐science CarbonTracker global inversion system, which assimilates (a) in situ measurements (IS), (b) the Orbiting Carbon Observatory‐2 (OCO‐2) v9 column CO2 (XCO2 ) retrievals over land (LNLG), (c) OCO‐2 v9 XCO2 retrievals ocean‐glint (OG), and (d) a combination of all these observational constraints (LNLGOGIS). We use independent CO2 observations from the Atmospheric Carbon and Transport (ACT)—America aircraft mission to evaluate the inversions. We diagnose errors in the flux estimates using the differences between modeled and observed biogenic CO2 mole fractions, influence functions from a Lagrangian transport model, Bayesian inference, and root‐mean‐square error (RMSE) and bias metrics. The IS fluxes have the smallest RMSE among the four products, followed by LNLG. Both IS and LNLG outperform the OG and LNLGOGIS inversions with regard to RMSE. Regional errors do not differ markedly across the four sets of posterior fluxes. The CarbonTracker inversions appear to overestimate the seasonal cycle of NEE in the Midwest and Western Canada, and overestimate dormant season NEE across the Central and Eastern US. The CarbonTracker inversions may overestimate annual NEE in the Central and Eastern US. The success of the LNLG inversion with respect to independent observations bodes well for satellite‐based inversions in regions with more limited in situ observing networks. Plain Language Summary: Biological CO2 fluxes, an important component of the earth's climate system, remain uncertain, especially at continental and sub‐continental spatial domains. Different global CO2 observing systems imply significantly different net biological fluxes of CO2 . We use independent CO2 measurements from an extensive multi‐seasonal aircraft campaign to evaluate biological CO2 flux estimates derived from four different observational systems entered into a common data analysis system. The observations include both ground and satellite‐based measurements. We found that one of the the satellite‐based CO2 estimates performs nearly as well as the estimates based on ground‐based measurements. This suggests that the satellite data may serve to estimate regional variations in biological CO2 fluxes in portions of the globe with more limited ground‐based observing networks. The inversions all appear to overestimate dormant season release of biological CO2 to the atmosphere, thus may underestimate the net uptake of CO2 by ecosystems in the Central and Eastern United States. Key Points: In situ measurements and the land nadir/land glint inversions are the most reliable products of CarbonTracker in temperate North America, superior to ocean‐glint or LNLGOGIS inversions Errors in these CarbonTracker regional flux estimates are not strongly dependent on the observational data sources CarbonTracker overestimates seasonal net ecosystem exchange (NEE) for the Eastern and Central US, thus the annual NEE may underestimate continental uptake of CO2